Efforts to increase the self-efficacy of pregnant women in caring for newborns in Karawang Regency - Jundra Darwanty; Ani Mardianti; Retno Dumilah (Community Empowerment, 2023)
Not all expectant mothers can carry out their roles without fear and anxiety. High and long-lasting anxiety can have a negative impact on the health of the mother and her baby. This community service activity aims to increase self-efficacy, knowledge, and skills of Posyandu cadres and expectant mothers in newborn care. This activity was carried out in stages including 1) preparation, including consultation, coordination and workshops, 2) implementation, through training at each posyandu on baby's cord care, bathing, changing swaddles and diapers, and 3) evaluation with an assessment of readiness cadres and pregnant women in caring for newborns. The result of this activity is an increase in the knowledge and self-efficacy of cadres and pregnant women in caring for newborns at Posyandu Delima 27 and Delima 24, Karawang Regency.